(untitled) (Nucleus, 2019)
Information that seeks biological alternatives in arugula cropping are scarce in Rondônia state cultivation of arugula. The objective of this study was to evaluate the agronomic characteristics of arugula as a function of seed inoculation with Azospirillum brasilense, algae extract (Ascophyllum nodosum) and co-inoculation (A. nodosum with A. brasilense) in Vilhena, Rondônia, Brazil. The experiment was carried out from March to April 2018, at the Faculdade da Amazônia, Vilhena, Rondônia, Brazil. The experimental design was completely randomized with four treatments and five replicates. The treatments tested were: 1 - control: without inoculant use; 2- seed treatment with A. brasilense; 3- seed treatment with algae extract; 4- seed treatment with co-inoculation (A. brasilense with A. nodosum). The evaluated characteristics were fresh leaf mass, fresh petiole mass, fresh root mass, fresh shoot mass, root/shoot ratio, leaf area, dry leaf mass, dry petiole mass, dry root mass, dry shoot mass and dry mass of the total plant. The largest arugula leaf area was obtained with co-inoculation of A. brasilense and A. nodosum. The highest root/shoot ratio was obtained in the treatment with the control. The highest dry mass of the total plants was obtained in the treatments with A. brasilense and co-inoculation. Co-inoculation of A. brasilense with A. nodosum is recommended.